Features of the Criminal Procedural Activities of the Court in the Resolution of Issues Related to the Execution of the Verdict of a Foreign State Court - Viktor I. Kachalov (Сибирское юридическое обозрение, 2017)
The article examines the specifics of judicial activity, its nature and subject matter, the specificity of the evidence in cases on the resolution of issues related to the execution of the sentence of a foreign state court, concludes with the peculiarities of the corrective activity of the court in the enforcement of the sentence of a foreign state.